Iesose” Isolation And Structure Elucidation Of Novel Nonasaccharide From Gaddi Sheep’s Milk - Sanyogita Shahi, Harvinder Kumar Singh, Desh Deepak, Shirish Kumar Singh (Drugs and Cell Therapies in Hematology, 2021)
The composition of milk varies from mother to mother in different ruminants but in general milk contains 85-90% of water and 13% of other nutrients, including fats, proteins and carbohydrates. Milk is a rich source of carbohydrate called oligosaccharides, one of the many different sugars in milk. These sugars are responsible for biological effects, such as providing energy for growing babies or contributing to organ development. Oligosaccharides are main components of milk and their bio-active properties like: prebiotics, anti-infective, and immune system modulators and as a possible source of sialic acid for neural concernment. In all mammals’ cow and buffalo is the major source of milk cattle of north India. Buffalo milk shows physicochemical properties like higher content of fatty acids and proteins which is different from that of other mammals. In Buffalo milk oligosaccharide propel distinct stimulation of antibody, delayed-type hypersensitivity which react to sheep red blood cells in BALB/c mice. This also stimulates non-specific immune response of the animals i.e., macrophage migration index. In the present process Gaddi sheep’s milk was collected and processed through the modified method of Kobata and Ginsburg followed by gel filtration, high performance liquid chromatography and repeated column chromatography, which led to isolation of a novel nonasaccharide, named as Iesose. The result obtained from chemical degradation, chemical transformation along with advanced spectroscopic data suggested that it was a nonasaccharide. Further the structure was reconfirmed by different methods of NMR like: 1H, 13C and 2D NMR (COSY, TOCSY and HSQC) techniques along with mass spectrometry. The structure of Iesose was deduced as: